1988
DOI: 10.1002/eji.1830181009
|View full text |Cite
|
Sign up to set email alerts
|

Application of recombinant granulocyte‐macrophage colony‐stimulating factor has a detrimental effect in experimental murine leishmaniasis

Abstract: The purpose of this study was to evaluate the effect of recombinant granulocyte-macrophage colony-stimulating factor (rGM-CSF) on BALB/c mice infected s.c. with the intracellular pathogen Leishmania major. Daily i.p. application of 1 microgram rGM-CSF for 21 days following the infection led to an aggravated course of the disease in most animals. In no case was a therapeutic effect observed. In vitro analysis revealed that the parasite burden was approx. 2- to 7-fold higher in the infected lesions, in the lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…Interestingly, Leishmania antigens presented by GM-CSF-derived macrophages could protect susceptible mice against challenge with L. major by activating TH1 cells (15). While GM-CSF demonstrates a clear-cut leishmanicidal activity in vitro and in vivo in the L. donovani model (29,54), the results obtained in the literature with L. major were more conflicting, suggesting that GM-CSF may play a positive (2,15,19,21), neutral (12), or negative (18,47) role in host defense. Our results indicated that recombinant GM-CSF parasites were eliminated much more rapidly inside macrophages compared to control cells and that this occurred independently of the macrophage type used for infection ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Leishmania antigens presented by GM-CSF-derived macrophages could protect susceptible mice against challenge with L. major by activating TH1 cells (15). While GM-CSF demonstrates a clear-cut leishmanicidal activity in vitro and in vivo in the L. donovani model (29,54), the results obtained in the literature with L. major were more conflicting, suggesting that GM-CSF may play a positive (2,15,19,21), neutral (12), or negative (18,47) role in host defense. Our results indicated that recombinant GM-CSF parasites were eliminated much more rapidly inside macrophages compared to control cells and that this occurred independently of the macrophage type used for infection ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The "safe-target" hypothesis, where increased numbers of immature myeloid cells provide a site for rapid multiplication of amastigotes, has been frequently applied to infections with L. major (13,33). In this model, both susceptibility to infection and myelopoiesis are regulated by IL-3 and GM-CSF (17,19,24), and the parasite has a tropism for immature myeloid cells (11,33). In contrast, L. donovani infection occurs most readily in mature macrophage populations (11), IL-3 is limiting during infection (reference 21 and this report), and GM-CSF is required for resistance in the liver (35).…”
Section: Discussionmentioning
confidence: 99%
“…In experimental L. donovani infection, the opposite appears to be the case (5,24,37,38). In addition, GM-CSF has been reported to enhance the growth of L. mexicana promastigotes (but not amastigotes) in a cell-free system (39), fail to induce antileishmanial effects in vitro in macrophages parasitized by L. tropica and L major (40,41), and exacerbate cutaneous L. major lesions when used as treatment in vivo (41). These results and the possibility that fresh monocytes mobilized by GM-CSF and attracted to infected tissues may provide additional "safe targets" for L. major (35) or L. mexicana (39) have raised concem…”
Section: Discussionmentioning
confidence: 99%